Hubungan Kemampuan Membaca Sastra dengan Kemampuan Menulis Karangan Narasi Siswa Kelas X SMA Negeri 1 Lubuk Basung - Yeni, Retna; Gani, Erizal; Afnita, Afnita (Universitas Negeri Padang, 2013)
The aim of this research is to (1) describe the ability of students class X SMA N 1 Negeri Lubuk Basung in reading literature. (2) Explain the ability of students class X SMA N 1 Negeri Lubuk Basung in writing narrative text. (3) analize the relation between the ability of reading literature and the ability of writing narrative text of students class X SMA N 1 Negeri Lubuk Basung. The method that used in this research is correlation study method. Based on the research result, it can be concluded: first, reading literature ability of students class X SMA N 1 Negeri Lubuk Basung qualified in enough position (61, 48). Second, writing narrative text ability of students class X SMA N 1 Negeri Lubuk Basung qualified in almost enough position (49, 5). Third, there is a significant relation between the reading literature ability and writing narrative text ability of students class X SMA N 1 Negeri Lubuk Basung.